Measurements on hydrophobic and hydrophilic surfaces using a porous gamma alumina nanoparticle aggregate mounted on Atomic Force Microscopy cantilevers - Das, T.; Becker, Thomas; Nair, Balagopal (Elsevier Science SA, 2009)
Atomic Force Microscopy (AFM) measurements are extensively used for a detailed understanding ofmolecular and surface forces. In this study, we present a technique for measuring such forces, using an AFM cantilever attached with a porous gamma alumina nanoparticle aggregate. The modified cantilever was used to measure the forces of interaction of the aggregate with hydrophilic and hydrophobic surfaces. A strong force of attraction was observed between the aggregate and hydrophilic surfaces when the aggregate was kept dry. However, the force of interaction on the aggregate in wet form (water filled in pores) was larger when the adjoining surface had hydrophobic characteristics. The results presented in this study show the versatility of the current technique and indicate its usefulness in directly characterizing hydrophilic/ hydrophobic properties of nano-scale surfaces and patterns.